ETHICS FOR THE FUTURE? HUMAN RIGHTS AND RESPONSIBILITIES OF THE CURRENT GENERATION TOWARD FUTURE GENERATIONS (Andamios, Revista de Investigación Social, 2007)
Among the third generation of human rights, the appeal for a diachronic solidarity between the human community and the extrahuman natural world, and for a synchronstic one between the community of living human beings and hypothetical members of future human generations, has a significant place. This paper analyzes from a critical perspective the reasons for and against this proposal of duties and intergenerational ethical obligations in the context of a techno-scientific civilization, with the aim of grounding the current generation´s responsibility regarding the elaboration of a global ethics that could face the demands of future generations.
Keywords: Bioethics; human rights; intergenerational rights; responsibility; future